Legal Issues Regarding Dietary Supplement Regulation - Siripan, Somporn (Journal of Graduate MCU KhonKaen Campus, 2022)
This study aim was to study the implementation of government policies according to the consumer protection strategic plan Phase1,Revised Edition (2020-2022). In the study of consumer protection law, the researcher conducted a documentary research by conducting research, gathering information, principles and criteria from legal provisions, books, articles, journals, theses i.e.Civil and commercial Code, Criminal Code, Consumer Protection Act, B.E.2522 (1979), Responsibility for Damages Caused by Unsafe Goods Act,B.E.2551 (2008), Food Act, B.E.2522 (1979) Direct Sales and Direct Marketing Act, B.E.2545 (2002) Computer-Related Offenses Act (No.2), B.E.2560 (2017), Consumer Proceedings Act, B.E.2551 (2008), Notification of Ministry of Public HealthNo.293), B.E.2548 (2005) Re: Dietary Supplements. Notification of The ministry of Public HealthNo.309), B.E.2550 (2007) Re: Food supplements (No.2). The results of the study found that all dietary supplement Legislation focusses on measures.Controlling the fruit of food supplements and also help to heal consumer who have been violated whether it is life, body, health or rights to be treated fairly.